THE EXISTENCE OF CIVIC EDUCATION AND ARTIFICIAL INTELLIGENCE–BASED LEARNING MEDIA IN SUPPORTING ELEMENTARY STUDENTS’ SOCIAL-EMOTIONAL DEVELOPMENT - Nurleli Hairani Harahap; Seri Gustini; Hamka (PT. Jurnal Center Indonesia Publisher, 2026)
Elementary education plays a strategic role in shaping students’ character, civic attitudes, and social-emotional development. Civic Education is a fundamental subject for instilling democratic values, responsibility, and social awareness from an early age. Meanwhile, the advancement of digital technology, particularly Artificial Intelligence (AI)–based learning media, offers new opportunities to improve the quality of learning in elementary schools. This study aims to analyze the existence of Civic Education and the use of AI-based learning media in supporting students’ social-emotional development. This research employed a descriptive qualitative approach and was conducted at SD Negeri 0722 PTPN IV Lubuk Bunut. Data were collected through observation, interviews, and documentation. The findings indicate that Civic Education plays a significant role in fostering students’ social attitudes, empathy, and responsibility, while AI-based learning media enhance students’ learning motivation and engagement when implemented appropriately and in accordance with developmental stages. The integration of Civic Education, AI-based media, and developmental psychology perspectives contributes positively to students’ social-emotional development in elementary education.